Impact of microbiological processes on the cycling of Fe in Antarctic sea ice during Spring - Schoemann, Véronique; Lannuzel, Delphine; Becquevort, Sylvie; Tison, Jean-Louis; Trevena, Anne; de Jong, Jeroen; Delille, Bruno; Sauvée, M.-L.; Lancelot, Christiane; Chou, Lei (2006)
info:eu-repo/semantics/published